Chromothripsis in Treatment Resistance in Multiple Myeloma - Kyoung Joo Lee; Ki Hong Lee; Kyong-Ah Yoon; Ji Yeon Sohn; Eunyoung Lee; Hyewon Lee; Hyeon-Seok Eom; Sun-Young Kong (Genomics & Informatics)
Multiple myeloma (MM) is a malignant disease caused by an abnormal proliferation of plasma cells, of which the prognostic factors include chromosomal abnormality, β-2 microglobulin, and albumin. Recently, the term chromothripsis has emerged, which is the massive but highly localized chromosomal rearrangement in response to a one-step catastrophic event. Many studies have shown an association of chromothripsis with the prognosis in several cancers; however, few studies have investigated it in MM. Here, we studied the association between chromothripsis-like patterns and treatment resistance or prognosis. First, we analyzed nine MM cell lines (U266, MM.1S, RPMI8226, KMS-11, KMS-12-BM, KMS-12-PE, KMS-28-BM, KMS-28-PE, and NCI-H929) and bone marrow samples of four patients who were diagnosed with MM by next-generation sequencing-based copy number variation analysis. The frequency of the chromothripsis-like pattern was observed in seven cell lines. We analyzed the treatment-induced chromothripsis-like patterns in KMS-12-BM and KMS-12-PE cells. As a result, breakpoints and chromothripsis-like patterns were increased after drug treatment in the relatively resistant KMS-12-BM. We further analyzed the patients’ results according to the therapeutic response, which was divided into sensitive and resistant, as suggested by the International Myeloma Working Group. The chromothripsis-like pattern was more frequently observed in the resistant group. In the sensitive group, the frequency of the chromothripsis-like pattern decreased after treatment, whereas the resistant group showed increased chromothripsis-like patterns after the treatment. These results suggest that the chromothripsis-like pattern is associated with treatment response in MM.